Closed polynomials and saturated subalgebras of polynomial algebras - Arzhantsev, I.V.; Petravchuk, A.P. (Український математичний журнал, 2007)
The behavior of closed polynomials, i.e., polynomials f∈k[x₁,…,xn]∖k such that the subalgebra k[f] is integrally closed in k[x₁,…,xn], is studied under extensions of the ground field. Using some properties of closed polynomials, we prove that, after shifting by constants, every polynomial f∈k[x₁,…,xn]∖k can be factorized into a product of irreducible polynomials of the same degree. We consider some types of saturated subalgebras A⊂k[x₁,…,xn], i.e., subalgebras such that, for any f∈A∖k, a generative polynomial of f is contained in A. Досліджено поведінку замкнених поліномів, тобто таких поліномів f∈k[x₁,…,xn]∖k, що пiдалгебра k[f] є інтегрально замкненою в k[x₁,..., xn], у випадку розширень основного поля. З використанням деяких властивостей замкнених поліномів доведено, що кожен поліном f∈k[x₁,…,xn]∖k після зсувів на константи може бути розкладений у добуток незвідних поліномів одного й того ж степеня. Розглянуто деякі типи насичених підалгебр A⊂k[x₁,…,xn], тобто таких алгебр, що для будь-якого f∈A∖k породжуючий поліном для f міститься в A.